American Childhoods - Illick, Joseph E. (Book collections on Project MUSE., 2002)
"Synthesizing an enormous amount of secondary source material, this book is a stunning achievement ... This book would make an ideal classroom text and should be read by anyone interested in the history of childhood."--Choice